Finance and Development, September 1967. (Finance and Development; Finance and Development, 1967)
This paper focuses on the economic development in Taiwan. The paper highlights that it was under the Japanese that the first significant commercial development took place in Taiwan as the colony was transformed into a supplier of foodstuffs, particularly rice and sugar, for sale in Japan, in accordance with the normal views of that time of the role of a colonial dependency. The Japanese established an infrastructure in the form of power, communications, and water control systems. The last was an important contribution.